DETERMINANTS OF FDI LOCATION CHOICE IN CHINA: A CASE OF TAIWANESE FIRMS - Phạm Thị Ngọc Dung (Tạp chí Khoa học Đại học Đà Lạt)
The agglomeration of FDI in some specific locations in the host country, especially in emerging economies, might lead to the huge disparity in economic development between areas. Therefore, attracting FDI into less-developed areas outside the FDI agglomeration areas is an important mission for sustainable development. This research analyses the impact of location determinants such as market size, living standard, market growth, labour cost and labour availability on firms’ decision to locate FDI outside the FDI agglomeration areas. Moreover, the moderating impact of FDI experience on the relationship between location factors and location decisions will be considered based on the data of Taiwanese FDI in China during the period of 1999-2010.